Strategi Kebijakan Pemerintah Venezuela di Tengah Krisis - Nuryanti, Nuryanti; Salsabila, Salsabila (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
In the era of president Nicolas Maduro, the Venezuela faced economic crisis. It affects to social and economic decline. The govenment is in the chellenge of public trust and political instablity. The Maduro performance perceived as less effective and repressive that lead to the society questioning about government capacity to solve the problems. Thus, the authors are interested in explaining the efforts of the Venezuelan government in dealing with the crisis. The author uses descriptive qualitative research methods and data collection techniques based on literature study. The data source comes from the literature published by scholars and experts on Venezuelan politics and the Latin American economic crisis. The author notes several actions of the Venezuelan government in dealing with the economic crisis including: (1) economic policies reform; (2) diplomacy of foreign aid to China; (3) food price stabilization: (4) strengthening public health services; and (5) strengthening regional cooperation with organizations in the Latin American region.